2018
DOI: 10.1002/ece3.4237
|View full text |Cite
|
Sign up to set email alerts
|

Gene flow and Andean uplift shape the diversification of Gasteracantha cancriformis (Araneae: Araneidae) in Northern South America

Abstract: The Andean uplift has played a major role in shaping the current Neotropical biodiversity. However, in arthropods other than butterflies, little is known about how this geographic barrier has impacted species historical diversification. Here, we examined the phylogeography of the widespread color polymorphic spider Gasteracantha cancriformis to evaluate the effect of the northern Andean uplift on its divergence and assess whether its diversification occurred in the presence of gene flow. We inferred phylogenet… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
35
0
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 90 publications
2
35
0
4
Order By: Relevance
“…The phylogenetic analysis of nuclear and mitochondrial genomes revealed the presence of two different L. braziliensis populations in Colombia (clade 2 and clade 4) ( Figures 1B-E). We considered that the presence of these clades within Colombia can be associated with (i): the geographical localization of each clade; clade 4 genomes are located outside of mountain ecosystems (east Andes), while the clade 2 genome (Lb7864) occurs in Colombian mountain ecosystems (central cordillera) ( Figure 1A), indicating that the Andes might generate intraspecies diversification, as has been proposed for different arthropods, such as bees (Dick et al, 2004), butterflies (De-Silva et al, 2016;Chazot et al, 2018), arachnids (Salgado-Roa et al, 2018), Triatominae (Gomez-Palacio and Triana, 2014;Monsalve et al, 2016), Lutzomyia species (Gonzalez et al, 2014;Ferro et al, 2015) and plants, such as Phlegmariurus (Testo et al, 2019). (ii): Constant human displacement due to violence, armed conflict, or the deployment of military troops from areas of high endemicity (Ore et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The phylogenetic analysis of nuclear and mitochondrial genomes revealed the presence of two different L. braziliensis populations in Colombia (clade 2 and clade 4) ( Figures 1B-E). We considered that the presence of these clades within Colombia can be associated with (i): the geographical localization of each clade; clade 4 genomes are located outside of mountain ecosystems (east Andes), while the clade 2 genome (Lb7864) occurs in Colombian mountain ecosystems (central cordillera) ( Figure 1A), indicating that the Andes might generate intraspecies diversification, as has been proposed for different arthropods, such as bees (Dick et al, 2004), butterflies (De-Silva et al, 2016;Chazot et al, 2018), arachnids (Salgado-Roa et al, 2018), Triatominae (Gomez-Palacio and Triana, 2014;Monsalve et al, 2016), Lutzomyia species (Gonzalez et al, 2014;Ferro et al, 2015) and plants, such as Phlegmariurus (Testo et al, 2019). (ii): Constant human displacement due to violence, armed conflict, or the deployment of military troops from areas of high endemicity (Ore et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Sin embargo, las diferencias morfológicas encontradas entre localidades son evidentes y probablemente se relacionan con el gradiente altitudinal al que están expuestas las poblaciones localmente (https://colombiasa.com/geografia/ geografia.html). Las altas elevaciones en la cordillera Central actúan como barrera para las poblaciones en algunos grupos de animales que se distribuyen en las cordilleras de los Andes (Díaz et al, 2014;Mills et al, 2007;Salgado-Roa et al, 2018), y en el caso de la población de Lérida, su diferenciación morfológica podría estar asociada a que se encuentra ubicada al norte de la vertiente oriental de los Andes Centrales. Es importante resaltar que también las poblaciones de Cunday y Chaparral presentaron diferencias con el resto de poblaciones, que pueden estar relacionadas con las condiciones de aislamiento y distribución que presentan actualmente estas poblaciones, al ser las que presentan mayor distanciamiento geográfico de la localidad tipo en Ibagué, Tolima.…”
Section: Discussionunclassified
“…Algunos estudios en Amblypygi han mostrado que los sistemas ecológicos de islas y cavernas promueven la diversificación del grupo, debido al bajo flujo génico que se da entre poblaciones del interior y el exterior de cavernas, y entre islas (Quintero, 1981;Kraus, 2000;Prendini, 2001;Esposito et al, 2015). Por otra parte, se sabe que los Andes de Colombia son fuente de variaciones fenotípicas y actúan como barrera del flujo genético entre poblaciones de algunos grupos de animales (De-Silva et al, 2017;Díaz et al, 2014;Ferretti et al, 2011;Román-Valencia et al, 2009;Ruiz-C et al, 2011;Salgado-Roa et al, 2018), por lo que los resultados encontrados en este trabajo, sugieren que los Andes también promueven procesos de diversificación en los amblipígidos de Colombia.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…We used 80 adult females from the Caribbean islands for our morphological analyses. We coded a total of six color morphs -three that have been previously described within G. cancriformis by Gawryszewski (2007) (white, yellow, black and white), an all-black morph previously reported by Salgado-Roa et al, (2018), and two morphs that had not been previously reported (white and red stripes, black and yellow stripes) ( Figure 1). We ran a chi-squared Monte Carlo analysis to test the association between the coloration and spine number of individuals and their genetic variation and geographic locality.…”
Section: Geographic Genetic and Morphological Distancesmentioning
confidence: 99%